Distal Radius Fracture Fixation Outcome Covering With Proneter Quadratus Muscle Comparing to Non Covering - Awad, Omar Adel; AL-Mukhtar, Sadeq (Journal of Science in Medicine and Life, 2026)
Background: Distal radius fractures (DRF) are common upper limb fractures, often requiring surgical intervention. The role of pronator quadratus (PQ) muscle coverage in improving surgical outcomes remains unclear. This study aims to evaluate the impact of PQ muscle coverage on the functional and clinical outcomes of DRF treated with volar locking plate fixation. Methods: A comparative observational study was conducted at Al-Kindy Teaching Hospital in Baghdad, Iraq, from June 2023 to July 2024. Twenty patients with DRF were divided into two groups: Group A (with PQ muscle coverage) and Group B (without PQ muscle coverage). Data were collected prospectively at baseline and during follow-up (1 week, 2 weeks, 1 month, and 3 months post-surgery), focusing on demographics, complications, functional outcomes (measured by DASH and Modified Mayo Wrist Scores), pain, grip strength, range of motion, and overall functional status. Results: The mean age of participants was 53.5 years, Infection rates were similar between both groups (p = 0.581). Flexor tendon irritation was significantly lower in Group A (0%) compared to Group B (20%) (p = 0.006). No significant differences were observed in pain, grip strength, range of motion, or overall functional status between the two groups. At 3 months post-surgery, both groups showed substantial functional recovery, with the majority returning to regular activities. The Modified Mayo Wrist Score revealed no significant differences between the groups (p = 0.171). Conclusions: PQ muscle coverage did not significantly improve overall functional outcomes, including pain levels, grip strength, range of motion, or functional status. However, it did reduce the incidence of flexor tendon irritation.